Kondisi Fisika-Kimia Perairan Pulau Kabaena Kabupaten Bombana Sulawesi Tenggara - Roni Wardi; Musrifin Ghalib; Mubarak Mubarak (Dinamika Lingkungan Indonesia, 2017)
This research was conducted in December 2016 at Kabaena Island, Bombana Southeast Sulawesi which refers to data taken in August 2016. The aim the research is to provide an overview and information on the physical-chemical conditions of Kabaena waters. The method used in this study is a survey and determining the point of sampling by purposive sampling. Sampling physical-chemical parameters of waters us done at a distance of 500 meters from the beach towards the sea and the sample was measured in situ. Physical-chemical parameters were observed i.e. depth, brightness, turbidity, dissolved oxygen, salinity, acidity (pH), temperature, and flow. The results of show that physical-chemical parameters measured were 3-41 meters depth, water temperature ranged from 27oC – 32oC, salinity obtained in waters between 31‰ - 34‰, brightness values waters between 3 meters to 13 meters, the value of the degree of acidity 8, 24, dissolved oxygen concentration from 3.81 to 4.43 mg/l or 5.44 to 6.33 mg/l, turbidity levels are high at 0.97 NTU, and the velocity of 0.04 m/sec to 0, 62 m/sec with an average value of 0.19 m/sec. 3.2. Based on the research results physical-chemical parameters of the waters of Kabaena by comparison with Kepmen LH 2004, the condition of physical-chemical parameters of waters Kabaena still quite good to support the continuity of the life of the organism.